Extension and Severity of Self-Reported Side Effects of Seven COVID-19 Vaccines in Mexican Population - Camacho Moll, María Elena; Salinas Martínez, Ana María; Tovar Cisneros, Benjamín; García Onofre, Juan Ignacio; Navarrete Floriano, Gloria; Bermúdez de León, Mario (Frontiers in Public Health, 2022)
A few studies examined the comparative side effects of Coronavirus Disease-19 (COVID-19) vaccines. We compared the extension and severity of self-reported side effects of seven COVID-19 vaccines [BNT162b2 (Pfizer-BioNTech), ChAdOx1 (AstraZeneca), mRNA-1273 (Moderna), CoronaVac (Sinovac Life Sciences), Gam-COVID-Vac (Gamaleya's Sputnik V), Ad5-nCoV (CanSinoBIO), and Ad26.CoV2.S (Johnson & Johnson/Janssen)] in the Mexican population. We also evaluated the association of type of vaccine, sex, age, comorbidity, and history of allergies to the extent and severity of side effects. This was a cross-sectional study carried out online between August 12 and September 3, 2021 in Mexico. The first inclusion criterion was to receive a COVID-19 vaccine and the second, being at least 18 years old. The survey link was distributed via multiple social media platforms. We questioned about the type of vaccine and symptoms based on short-term side effects reported in the literature. Side effect extension was classified as local, systemic, or both. We asked about the need to take medicine, stop activities/miss work, or seek medical attention. Then, a severity index was constructed based on responses. Descriptive and stepwise multivariate logistic ordinal regression analyses were used to calculate odds ratio (OR) and 95% CI for each outcome adjusted by potential confounders. The mean age was 38.9 ± 11.0 years (n = 4,024). Prevalence of at least one side effect varied between vaccines and by a number of doses. At dose 1, ChAdOx1 was the vaccine with the highest rate of at least one side effect (85%) followed by Gam-COVID-Vac (80%). Both were associated to greater extension (adjusted OR 2.53, 95% CI 2.16, 2.96 and adjusted OR 2.41, 95% CI 1.76, 3.29, respectively) and severity of side effects (adjusted OR 4.32, 95% CI 3.73, 5.00 and adjusted OR 3.00, 95% CI 2.28, 3.94, respectively). Young age (<50 years), female sex, comorbidity, and history of allergies were associated with greater extension and severity, independent of the type of vaccine and potential confounders. At dose 2, mRNA-1273 was the vaccine with the highest rate of side effects (88%) and the only vaccine associated to greater extension (adjusted OR 2.88, 95% CI 1.59, 5.21) and severity of symptoms (adjusted OR 3.14, 95% CI 1.82, 5.43). Continuous studies are necessary to acknowledge more post-vaccine symptoms in different populations.